2021
DOI: 10.3390/ani11092751
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes of Solitary Housed Female Pygmy Slow Lorises (Nycticebus pygmeaus) after Introduction into Group Enclosures

Abstract: Pygmy slow lorises (Nycticebus pygmaeus) are threatened with extinction in the wild. Their nocturnal lifestyle and small size make them difficult to study in their natural habitat, but increasing evidence suggests that they are more social than previously thought. Our study was designed to assess the sociability of pygmy slow lorises by transferring six adult females from solo cages into environmentally enriched group home cages at the Japan Monkey Centre’s Slow Loris Conservation Centre. Two females were pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…At the moment, the low number of published papers dealing with (re)unions is unlikely to represent a high percentage of the actual cases of (re)unions taking place in zoological institutions worldwide. Moreover, published papers tend to deal mainly with highly charismatic social species (such as social primates, wild dogs and elephants [3,[12][13][14][15]), although solitary species can also be kept in groups or pairs in zoos, and such an approach has been found to be beneficial for at least some of them [8,[16][17][18][19]. For example, a quick search on Scopus (https://www.scopus.com/; accessed on 16 November 2021) with the introduction AND zoo AND cat AND social AND group as keywords rendered only one result: a paper on enrichment in tigers, including a general section on social housing [20], although two cases of a semiochemical being used during the introduction of tigers have been published elsewhere [2,21].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the low number of published papers dealing with (re)unions is unlikely to represent a high percentage of the actual cases of (re)unions taking place in zoological institutions worldwide. Moreover, published papers tend to deal mainly with highly charismatic social species (such as social primates, wild dogs and elephants [3,[12][13][14][15]), although solitary species can also be kept in groups or pairs in zoos, and such an approach has been found to be beneficial for at least some of them [8,[16][17][18][19]. For example, a quick search on Scopus (https://www.scopus.com/; accessed on 16 November 2021) with the introduction AND zoo AND cat AND social AND group as keywords rendered only one result: a paper on enrichment in tigers, including a general section on social housing [20], although two cases of a semiochemical being used during the introduction of tigers have been published elsewhere [2,21].…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this study was to examine the relationship between stress hormones, housing conditions, and behavior among adult female pygmy slow lorises confiscated from illegal markets. A previous study revealed that females were more social than expected and that their behaviors significantly changed once paired; these changes should be reflected in their hormonal profiles (Alejandro et al, 2021). Additionally, one of our subjects displayed stereotypical behavior (see Section 2), allowing us to assess the impact of housing conditions on hormones and stereotypies.…”
Section: Introductionmentioning
confidence: 89%
“…The collection of fecal samples (see below), as well as behavioral data, continued throughout the study. Details of the pairing process, the history of SLCC, the behavioral and physiological responses of male pygmy lorises, and the behavioral changes for the female pairings have been reported in detail elsewhere (Alejandro et al, 2021; Yamanashi et al, 2021). This study conformed to “The Guide for Animal Research Ethics” of the JMC, the legal requirements of Japan, and the ASP Principle for Ethical Treatment of Nonhuman Primates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations